Crystal structure of nilotinib, C28H22F3N7O. Issue 3 (14th August 2015) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of nilotinib has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Nilotinib crystallizes in space group P 1 (#1) with a = 4.518 14(3), b = 10.638 01(5), c = 13.703 77(8) Å, α = 68.8607(4), β = 82.1486(5), γ = 84.1978(5)°, V = 607.62(1) Å 3, and Z = 1. The most prominent feature of the structure is two strong hydrogen bonds. These form chains with a graph set C1, 1(13); the chains run along [111]. Several weak C–H···O hydrogen bonds also contribute to the packing. The powder pattern has been submitted to ICDD for inclusion in future releases of the Powder Diffraction File™.